Faktor-Faktor Yang Mempengaruhi Return Saham Perusahaan Pertambangan Batubara Di Bei Periode 2008-2015 - Rafail Widarko dan Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to determine the influence of debt to equity ratio, return on assets, return on equity and earning growth partially and simultaneously to stock return of coal mining companies listed on the Indonesia Stock Exchange during the period 2008-2015. The populations in this research are all companies of coal mining industry listed in Indonesia Stock Exchange. Sampling was done by purposive sampling method, consisting of 8 companies. Based on the type of data and analysis, this research is quantitative research and the data source used is secondary data. Data collection method used is direct observation method. Based on multiple linear regression test, it can be concluded that debt to equity ratio, return on assets, return on equity have significant and positive influence toward stock return with significant value below 0.05, while earning growth have no influence toward stock return with significant value 0.9. Simultaneously, all the independent variables significantly influence the stock return with significant value 0.000143. Based on the coefficient of determination can be concluded that all the independent variables affect the financial performance by 26.92%.